Crispy Krup / Nur Adlina Rajie and Tenku Nur Sufi Safiya Tenku Sulong Saputra - Rajie, Nur Adlina; Tenku Sulong Saputra, Tenku Nur Sufi Safiya (2023)
CrispyKrup is a start-up business launched by business partners that are committed to provide a variety of types of kerepek such as kerepek ubi pedas, tortillas jagung and popia udang. These are the types of food people can easily consume anytime and anywhere they go .Today, chips are consumed all year round as a side dish and are no longer just consumed during the festive season. According to Malaysian market trends, selling food can generate a lot of attention fromcustomers. Although CrispyKrup is based in Jitra, Kedah, this company prioritizes online sales, particularly through the Facebook platform. We specifically target people who are employed and looking for meals to share with their families. Our items are excellent for creating meal menus and for during the festive season. CrispyKrup, a startup business, uses effective marketing techniques to quickly create an apparent following on social media platforms. Regular product advertisements are primarily posted on our Facebook page. To further develop a personalized connection, we also communicate directly with clients via Facebook and WhatsApp channels. We have worked with J&T Malaysia, who are well-known for providing effective service, to ensure prompt and reliable delivery. We also offer COD (cash on delivery) service to our customers .Our approach focuses on delivering in good condition, high-quality products to our satisfied customers, and we place a great priority on customer happiness.